Seismogenic zone structure of the southern Middle America Trench, Costa Rica - DeShon, H.R. (2003)
The shallow seismogenic portion of subduction zones generates damaging large and great earthquakes. This study provides structural constraints on the seismogenic zone of the Middle America Trench offshore central Costa Rica and insights into the physical and mechanical characteristics controlling seismogenesis. We have located 300 events that occurred following the MW 6.9, 20 August 1999, Quepos, Costa Rica, underthrusting earthquake using a three-dimensional velocity model and arrival time data recorded by a temporary local network of land and ocean bottom seismometers. We use aftershock locations to define the geometry and characteristics of the seismogenic zone in this region. These events define a plane dipping at 19 that marks the interface between the Cocos Plate and the Panama Block. The majority of aftershocks occur below 10 km and above 30 km depth below sea level, corresponding to 30–35 km and 95 km from the trench axis, respectively. Relative event relocation produces a seismicity pattern similar to that obtained using absolute locations, increasing confidence in the geometry of the seismogenic zone. The aftershock locations spatially correlate with the downdip extension of the oceanic Quepos Plateau and reflect the structure of the main shock rupture asperity. This strengthens an earlier argument that the 1999 Quepos earthquake ruptured specific bathymetric highs on the downgoing plate. We believe that subduction of this highly disrupted seafloor has established a set of conditions which presently limit the seismogenic zone to be between 10 and 35 km below sea level.